Effect of phosphorous on the growth, optical, mechanical and thermal properties of L-alanine crystals - Maruthamuthu, Anbuchezhiyan; A, Arputhalatha; S, Ponnusamy; K, Syed Suresh Babu (Photonics Letters of Poland, 2015)
Single crystals of L-alanine were grown from aqueous solution with a small amount of orthophosphoric acid (H3PO4). The single crystal X-ray diffraction (XRD) analysis was employed to identify the cell parameters. The grown crystal was characterized by Energy Dispersive X-ray (EDX) spectrum. The UV-visible transmittance was recorded. The presence of a functional group was confirmed by FTIR analysis. The TGA/DTA studies showed the thermal properties of the crystals. The mechanical strength was analyzed by measuring microhardness of the grown compounds. The second harmonic generation of grown crystals was confirmed by the Kurtz-Perry method using an Nd:YAG laser. Full Text: PDF References D.S. Chemla, J. Zyss, (Eds.), Nonlinear Optical Properties of Organic Molecules and Crystals (Academic Press, Orlando, New York, 1987). C. Razzetti, M. Ardoino, L. Zanotti, M. Zha, C. Paorici, "Solution Growth and Characterisation of L-alanine Single Crystals", Cryst. Res. Technol. 37, 456 (2002). CrossRef E. Ramachandran, S. Natarajan, "Synthesis of L-valine crystals", Cryst. Res. Technol. 44, 641 (2009). CrossRef K. Srinivasan, "Growth of non-linear optical ?-glycine single crystals and their characterization", J. Arumugam, Optic. Mater. 30, 40 (2007). CrossRef Sd. Z. Ali Ahamed, G.R. Dillip, L. Manoj, P. Raghavaiah, B. Deva Prasad Raju, "Growth and characterization of new NLO material: L-serine sodium nitrate", Phot. Letters Poland 2(4), 183 (2010). CrossRef S. Dhanuskodi, J. Ramajothi, "Crystal growth, thermal and optical studies of L-histidine tetrafluoroborate: A semiorganic NLO material", Cryst. Res. Tech. 39, 592 (2004). CrossRef R. Ittyachan, P. Sagayaraj, "Growth and characterization of a new promising NLO L-histidine bromide crystal", J. Cryst. Growth 249, 557 (2003). CrossRef M. Lydia Caroline, R. Sankar, R.M. Indirani, S. Vasudevan, "Growth, optical, thermal and dielectric studies of an amino acid organic nonlinear optical material: l-Alanine", Mater. Chem. Phys. 114, 490 (2009). CrossRef G. Ravi, S. Anbukumar, P. Ramasamy, "On the growth and characterization of mixed crystals of the triglycine sulphate family", J. Cryst. Growth 133, 212 (1993). CrossRef N. Nakatani, M. Yoshio, "Crystal Form of Phosphoric-Acid-Doped Triglycine Sulfate", Jpn. J. Appl. Phys. 35, L 508 (1996). CrossRef N. Nakatani, M. Yoshio, "Doping of Phosphoric Acid into Ferroelectric Triglycine Sulfate Crystal", Jpn. J. Appl. Phys. 35, 5752 (1996). CrossRef A. Saxena, V. Gupta, K. Sreenivas, "Characterization of phosphoric acid doped TGS single crystals", J. Cryst. Growth 263, 192 (2004). CrossRef M. Anbuchezhiyan, S. Ponnusamy, C. Muthamizhchelvan, C.C. Kanakam, S.P. Singh, P.K. Pal, P.K. Datta, "Etching, micro hardness and laser damage threshold studies of a nonlinear optical material L-valine", Eur. Phys. J. Appl. Phys. 58, 10201 (2012). CrossRef K. Seethalakshmi, S. Perumal, "Studies on growth, structure and optical studies of undoped and KBr doped Lalanine single crystals", Recent Research Sc. Techn. 4(6), 13 (2012). DirectLink Ferdousi Akhtar, Jiban Podder, "A Study on Growth, Structural, Optical and Electrical Characterization of L-alanine Single Crystal for Optoelectronic Devices", Research J. Physics 6(2), 31 (2012). CrossRef K. Sangwal, B. Surowska, "Study of indentation size effect and microhardness of SrLaAlO4 and SrLaGaO4 single crystals", Mater. Res. Innovat. 7, 91 (2003). DirectLink S.K. Kurtz, T.T. Perry, "A Powder Technique for the Evaluation of Nonlinear Optical Materials", J. Appl. Phys. 39, 3798 (1968). CrossRef